KETENTUAN PENAHANAN IJAZAH PEKERJA SEBAGAI SYARAT TERTENTU DALAM PERJANJIAN KERJA - Hidayah, Ardiana (Solusi, 2018)
Employment arrangements are regulated for the fulfillment of fundamental rights and protections for workers and workers. An employment agreement is established between workers and employers who meet the terms of employment, rights and obligations of the parties. The provisions of Law Number 13 Year 2003 regarding Manpower do not regulate whether or not the company holds the employee's diploma. This has resulted in a legal vacuum regarding whether or not a diploma may be imposed. Detention of diploma of worker / employee by the company, is allowed, as long as it becomes agreement between both parties. The opportunity to make the employer to arrest the original diploma of workers as a condition of acceptance of workers to work based on the customs that occur in the world of work and on the basis of freedom of contract, on the other hand the detention of diplomas can be detrimental to the workers because it forms a violation of Human Rights